Tetrahedral tetrakis(p-ethynylphenyl) group IV compounds in microporous polymers: effect of tetrel on porosity - Uptmoor, Andrea Christina; Geyer, Florian Ludwig; Rominger, Frank; Freudenberg, Jan; Bunz, Uwe H. F. (ChemPlusChem, 2018)
Article “Tetrahedral Tetrakis(p-ethynylphenyl) Group IV Compounds in Microporous Polymers: Effect of Tetrel on Porosity” Detailed information of the J-GLOBAL is a service based on the concept of Linking, Expanding, and Sparking, linking science and technology information which hitherto stood alone to support the generation of ideas. By linking the information entered, we provide opportunities to make unexpected discoveries and obtain knowledge from dissimilar fields from high-quality science and technology information within and outside JST.
Gesehen am 21.02.2020